2018
DOI: 10.1002/pssa.201700957
|View full text |Cite
|
Sign up to set email alerts
|

Cu2ZnSnSe4: How Far Does Off‐Stoichiometry Go?

Abstract: Polycrystalline powder samples of eight very far off-stoichiometric Cu 2 ZnSnSe 4 (CZTSe) compounds (off-stoichiometry types A-D) are grown using the solidstate reaction method in evacuated silica tubes. An additional thermal annealing is performed, in order to study the influence of annealing on the phase content and stoichiometry of the CZTSe phases formed under these conditions. The structural characterization of the synthesized materials before as well as after annealing is carried out by powder X-ray diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The limits of the structural flexibility of the kesterite-type structure were examined in CZTSe [18]. In this study it was shown that the synthesis of CZTSe powder material with an intended far off-stoichiometric composition (0.4Cu/(Zn+Sn)2.0 and 0.33Zn/Sn3) ended up in much less off-stoichiometric kesterite-type phases and co-existing secondary phases.…”
Section: Stoichiometry Deviations and The Off-stoichiometry Modelmentioning
confidence: 99%
“…The limits of the structural flexibility of the kesterite-type structure were examined in CZTSe [18]. In this study it was shown that the synthesis of CZTSe powder material with an intended far off-stoichiometric composition (0.4Cu/(Zn+Sn)2.0 and 0.33Zn/Sn3) ended up in much less off-stoichiometric kesterite-type phases and co-existing secondary phases.…”
Section: Stoichiometry Deviations and The Off-stoichiometry Modelmentioning
confidence: 99%
“…Particularly, the highest performing devices reported so far have been Cu‐poor, Sn‐stoichiometric, and Zn‐rich composition, while Zn‐poor and/or Cu‐rich conditions lead to poor efficiency solar cells. Due to the importance of composition in the conversion efficiency of kesterite, and its intimate relationship with defects and secondary phases formation, Lafond et al first introduced a classification of compositional‐types materials, lately extended by Gurieva et al as is shown in Figure . Up to 12 compositional‐type kesterites were proposed, each of them corresponding to different cationic balances (combining all possible poor and rich regions for each cation) and including a detailed description of the most probable secondary phases and intrinsic point defects formation .…”
Section: Challenges and Perspectives: How To Improve The Kesterite Efmentioning
confidence: 99%
“…Due to the importance of composition in the conversion efficiency of kesterite, and its intimate relationship with defects and secondary phases formation, Lafond et al first introduced a classification of compositional‐types materials, lately extended by Gurieva et al as is shown in Figure . Up to 12 compositional‐type kesterites were proposed, each of them corresponding to different cationic balances (combining all possible poor and rich regions for each cation) and including a detailed description of the most probable secondary phases and intrinsic point defects formation . As a remarkable property of this material, Valle Rios et al have shown the flexibility of kesterite‐type structure, which can self‐adapt from copper‐poor up to copper‐rich compositions without any structural change except in terms of cation distribution …”
Section: Challenges and Perspectives: How To Improve The Kesterite Efmentioning
confidence: 99%
See 1 more Smart Citation
“…where only the CuInSe 2 /ZnSe ratio was varied. However, in previous publications have been shown that different Cu concentrations also influence the properties of chalcogenides (secondary‐phase formation, defect formation, and structural polytype formation ) and have a great impact on absorber properties and solar cell efficiency. In line with this, we performed a detailed investigation of structural properties of CZISe with different Cu content and correlated them with various features found in Raman scattering spectra.…”
Section: Introductionmentioning
confidence: 99%